Grapefruit Oil and Cobalt Nitrate-Loaded Polyurethane Hybrid Nanofibrous Scaffold for Biomedical Applications - Mani, Mohan Prasath; Mohd Faudzi, Ahmad Athif; Mohamaddan, Shahrol; Ismail, Ahmad Fauzi; Rathanasamy, Rajasekar; Ayyar, Manikandan; Jaganathan, Saravana Kumar (Frontiers in Materials, 2022)
The goal of this work is to fabricate a new composite based on polyurethane (PU), grapefruit (GP) oil and cobalt nitrate (Co(NO3)2) using electrospinning technique. Morphology results revealed the reduction in the fiber diameter of the composites compared to pristine PU control. The interaction of PU with the GP and Co(NO3)2 was confirmed by hydrogen bond formation as evident in infrared analysis. The fabricated PU/GP composites depicted more hydrophobic behaviour while PU/GP/Co(NO3)2 showed hydrophilic behaviour than the pristine PU. Atomic force micrographs (AFM) revealed that developed composites showed a decrease in the surface roughness (Ra) compared to PU. The addition of GP and Co(NO3)2 improved the mechanical strength of the pristine PU. The blood compatibility assays concluded the increase in blood clotting levels and also less toxic nature of the fabricated composites compared to the pristine PU. Hence the newly designed composites possessing outstanding physicochemical and biological properties may be used as a potential candidate for scaffolding in tissue engineering applications.